1997
DOI: 10.1243/0954410971532541
|View full text |Cite
|
Sign up to set email alerts
|

Three component velocity measurements of an isothermal confined swirling flow

Abstract: A two-component fibre-optic laser Doppler velocimeter (LDV) system has been employed to measure the flowfield characteristics of a confined, isothermal strongly swirling flow in a combustor model. The primary objectives are to understand such complex flowfields and to provide complete benchmark data for comparisons with numerical predictions based on practical models for turbulent swirling flows, and thereby guide the development of such models. For this confined strongly swirling flow, the measurements show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In particular, in confined pipe flow, a number of experimental studies (e.g. [1]) have observed that in some cases the recirculation zone is not highly localised, but rather has a long "tail" of weak reverse flow that persists far downstream of the front stagnation point, a phenomenon for which no explanation has apparently been proposed to date. However, the porous rotating disk flow with injection considered here has the right features of a stagnation point and an outer reverse axial flow, which suggests the following qualitative explanation.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in confined pipe flow, a number of experimental studies (e.g. [1]) have observed that in some cases the recirculation zone is not highly localised, but rather has a long "tail" of weak reverse flow that persists far downstream of the front stagnation point, a phenomenon for which no explanation has apparently been proposed to date. However, the porous rotating disk flow with injection considered here has the right features of a stagnation point and an outer reverse axial flow, which suggests the following qualitative explanation.…”
Section: Discussionmentioning
confidence: 99%
“…The flow rate system was controlled using an in-house LabVIEW program to guarantee the reliability and reproducibility of the results. The Sauter mean diameter (SMD) of the majority of droplets from this Danfoss commercial nozzle is less than 60 µm, and the corresponding Stokes number of the majority of droplets was calculated to be ≪1 [23,24], making the spray droplets a good tracer for the flow field measurements in this work. The conditions of the test cases are listed in Table 1, and both non-reacting and reacting flows were conducted and compared for every case.…”
Section: Combustor Facilitymentioning
confidence: 98%
“…where, đťś• đť‘“ is the distance between the two fringes and đť‘“ đť‘‘ is measured signal frequency Depending on the location of the probe volume, in the present study, the average data rate of 500 samples/s is maintained for all the measurements. To reduce the statistical uncertainties in the measurement, a around 5000 realizations are collected at each measurement location, as suggested in (Ahmed 1997). Finally, flow sizer software provided by TSI Inc, is used to acquire, and analyse the data.…”
Section: 𝑢 = 𝜕 𝑓 𝑓 𝑑mentioning
confidence: 99%